Economic Partnership Agreements and the Export Competitiveness of Africa - Brenton, Paul; Hoppe, Mombert; Newfarmer, Richard (World Bank, Washington, DC, 2012)
Trade can be a key driver of growth for African countries, as it has been for those countries, particularly in East Asia, that have experienced high and sustained rates of growth. Economic partnership agreements with the European Union could be instrumental in a competitiveness framework, but to do so they would have to be designed carefully in a way that supports integration into the global economy and is consistent with national development strategies. Interim agreements have focused on reciprocal tariff removal and less restrictive rules of origin. To be fully effective, economic partnership agreements will have to address constraints to regional integration, including both tariff and non-tariff barriers; improve trade facilitation; and define appropriate most favored nation services liberalization. At the same time, African countries will need to reduce external tariff peak barriers on a most favored nation basis to ensure that when preferences for the European Union are implemented after transitional periods, they do not lead to substantial losses from trade diversion. This entails an ambitious agenda of policy reform that must be backed up by development assistance in the form of "aid for trade."